Variable Platelet Response to Low-dose ASA and the Risk of Limb Deterioration in Patients Submitted to Peripheral Arterial Angioplasty - Mueller, Michael Rolf; Salat, Andreas; Stangl, Petra; Murabito, Marco; Pulaki, Sad; Boehm, Dagmar; Koppensteiner, Renate; Ergun, Erdem; Mittlboeck, Martina; Schreiner, Wolfgang; Losert, Udo; Wolner, Ernst (Thrombosis and Haemostasis, 1997)
A group of 100 patients with intermittent claudication (70 male, 30 female), treated with 100 mg ASA per day, were followed over 18 months after elective percutaneous balloon angioplasty. Platelet function was monitored over a period of 12 months by corrected whole blood aggregometry (CWBA). Upon stimulation by arachidonic acid (AA), adenosine diphosphate (ADP) and collagen, CWBA-results were obtained by an electronic acquisition and evaluation system correcting for hematocrit and platelet count of the blood sample.All patients showed a completely inhibited platelet response to AA stimulation. Comparison of the CWB A-results with clinical parameters revealed that reocclusions at the site of angioplasty occurred exclusively in male patients for which CWBA failed to prove an inhibition of aggregation upon both agonists, ADP and collagen, and for these patients the risk of complication is at least 87% higher (p = 0.0093).Only 40% of male patients show the expected effect of ASA on in vitro platelet aggregation at any given point in time and CWBA is capable of predicting those male patients which are at an elevated risk of reocclusion following peripheral angioplasty.